Off-label use of a reversed flared endurant iliac limb stengraft for the management of a life-threatening internal iliac artery aneurysm rupture. (October 2014) - Gemayel, Gino; Murith, Nicolas; Kalangos, Afksendiyos
We report a case of a life-threatening internal iliac artery aneurysm rupture managed successfully with an on-table reversed flared iliac limb stentgraft and embolization. This easily off-the-shelf reproducible technique avoids using a more complex and expensive bifurcated aorto-iliac graft and could be a good solution in emergency situation where a custom graft is not available.